Penatalaksanaan Fisioterapi Pada Kondisi Cervical Root Syndrome E.C Spondylosis Cervical 4-6 Di Pku Muhammadiyah Yogyakarta - Sifaunnajwah, Lungguh; , Dwi Rosella Komala Sari, S.Fis.,M. Fis (2015)
Background: Cervical Root Syndrome is limited pain in cervical region, which is characterized by an increase in pain, limitation of motion, muscle spasm, and functional limitations. Modalities are given to this condition Infra Red (IR) and Transcuteneous Electrical Nerve Stimulation (TENS). Objective: To know the benefits of modalities IR and TENS in reduces the pain, improving ROM, reduces the muscle spasm, and increase functional activity. Methods: Physiotherapy methods used in the case that the modalities IR and TENS. The evaluation was done by the method of measurement of pain (VDS), ROM measurement (measuring goneometry), muscle spam (palpation), and functional activity (Neck Disability Index). Results: After 6 treatments of therapy showed a decrease in pain relief press T1: moderate pain to T6: mild pain, motion pain T1: moderate pain to T6: mild pain; increase range of motion cervical extention T1:30° to T6:35°, dexta rotation T1: 45° to T6:50°; reduces the muscle spasm T1: had muscle spasm fixed T6: decreased muscle spam; increase in functional activity T1: 50% to T6: 24%. Conclusion: In the case of modalities IR and TENS can reduces the pain, improving ROM, reduces the muscle spasm, and increase functional activity. Keywords: Cervical Root Syndrome, Spondylosis, IR, TENS.